2020
DOI: 10.3390/agriculture10050162
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Root Temperature on Growth, Physiology, and Accumulation of Bioactive Compounds of Agastache rugosa

Abstract: Plants respond to root temperature stresses by producing antioxidants as a defense mechanism. Since a number of these are phytochemicals with enhancing effects on human health, we examined the effects of 4 root-zone temperature (RZT) treatments (10, 20, 28, and 36 °C) on plant growth and the main bioactive compound concentrations in each organ of Agastache rugosa plants. We aimed to determine the optimal RZT treatment to increase bioactive compound concentrations with no deleterious effects on plant growth. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Similar to our results, root-zone cooling at 20 • C increased the biomass of aeroponically grown lettuce from that in plants with ambient conditions (24 • C to 38 • C) in a tropical greenhouse [22]. Since the roots of plants are more sensitive to heat stress than the above-ground parts, the high rootzone temperature can easily damage the root, which can restrict the length and diameter of the stem [24]. High root-zone temperature (27.5 • C) resulted in water and nutrient loss in tomatoes (Solanum lycopersicum L.), which ultimately led to a reduction in plant growth [25].…”
Section: Temperature and Cultivar Effect On Plant Growth Parameterssupporting
confidence: 88%
“…Similar to our results, root-zone cooling at 20 • C increased the biomass of aeroponically grown lettuce from that in plants with ambient conditions (24 • C to 38 • C) in a tropical greenhouse [22]. Since the roots of plants are more sensitive to heat stress than the above-ground parts, the high rootzone temperature can easily damage the root, which can restrict the length and diameter of the stem [24]. High root-zone temperature (27.5 • C) resulted in water and nutrient loss in tomatoes (Solanum lycopersicum L.), which ultimately led to a reduction in plant growth [25].…”
Section: Temperature and Cultivar Effect On Plant Growth Parameterssupporting
confidence: 88%
“…High values for bio-active compounds possessed by phog plant might be due to its resource poor habitat in The Thar Desert which includes high and low temperature, extremly resource poor soil, soil salinity and a prolonged drought period. A recent report of Lam et al (2020) support this hypothese, they found that higher root zone temperature (28 ºC) drastically improved the accumulation of bioactive compounds in Agastache rugosa. Correlation analysis for phenolics, flavonoids and total antioxidant activity of different plant parts of C. polygonoides exhibited linear positive association among them (r = > 0.900) (Table 3).…”
Section: Resultsmentioning
confidence: 73%
“…For example, Poire et al [29] reported that the leaf area and shoot fresh weight of Ricinus communis plants at lower root temperatures decreased throughout the experiment. In the experiment of Agastache rugosa, all plant growth parameters were restricted to cold root stress [13]. Plant growth of red leaf lettuce (Lactuca sativa L. cv.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that long-term root cooling improves nutritional quality by increasing the levels of beneficial functional plant constituents. For example, after a 24-day root temperature treatment, the rosmarinic acid and acacetin concentration of Agastache rugosa was highest at 10 • C root temperature [13]. In hydroponically grown carrots, a 14-day treatment with an elevated nutrient solution temperature increased the total phenolic compounds and soluble solid content [10].…”
Section: Introductionmentioning
confidence: 99%